Efficiency at various length 1 at % neodymium doped yttrium orthovanadate (Nd:YVO4) crystal - Andrew, Shirley Arvilla (2011)
Orthovanadate crystal is well known as a gain medium. However in scale-up the output power some parameters of the crystals have to be considered. This included the thickness or the length of the bar crystal. Therefore the aim of this project is to investigate best choice of length of 1 at % Nd:YVO4 crystal for the best laser performance. In attempt to achieve this goal, various lengths of bar crystal were under studied including 1.15, 3.00 and 10.00 mm. The crystals were longitudinally pumped by diode laser. The laser output was measured using powermeter, spectrum analyzer and CCD video camera. The beam spot of the laser outputs were recorded using CCD video camera. The Nd:YVO4 output beam spectrum centered at 1063.93 nm with linewidth of 0.70 nm. The output power for 1.15 and 3.00 mm crystals showed spontaneous emission in the initial stage. This followed by stimulated emission after exceeding threshold point. In the case for 10.00 mm crystal merely shows the spontaneous emission process. The limited pumping power does not allow lasing to occur from 10.00 mm crystal. The optimized length of 1 at % Nd:YVO4 crystals was found to be from the 3.00 mm crystal with slope efficiency of 4.51% and threshold power of 1921 mW. Meanwhile for 1.15 mm crystal manage to produce an efficiency of 1.07 % with threshold power of 2400 mW. The exciting beam for 10.00 mm crystal was dissipated and dispersed in the bulk of crystal causing spontaneous without stimulated emission.